The life story: A social qualitative research method and its application in tourism management studies - González Macías, Carlos Jesús; Cuevas Contreras, Tomás Jesús (RITUR - Revista Iberoamericana de Turismo, 2019)
This present paper approaches the relevance of the life story as a social qualitative research method and the benefit it brings when applicated in tourism management studies. A literature review was made to determinate which is the role of this particular research method when performing a study in the social sciences field, as well in tourism management. This method leads to a better understanding of a person’s own perception of its story, based in lived experiences inside, and outside, the tourism business ambience. For this issue, speaking of social responsibility and ethics in the tourism management qualitative research discipline, allows to conceptualize a vision which permits an adequate performance of a study that involves direct interaction with persons. This study contributes in a significant manner to consider the life story as a reliable qualitative research method for the construction of a data analysis, leading to remarkable results that will produce a major impact in science, mainly in tourism management studies.